SUKUK RITEL SYARIAH SEBAGAI INSTRUMEN PEMBIAYAAN NEGARA : EVALUASI HISTORIS DAN STRATEGI PENGUATAN DI ERA DIGITAL - Ria Nelta Febriyanti (Program Studi Ekonomi Syariah, 2025)
Retail Sukuk (Sukuk Ritel Syariah/SR) is a sharia-compliant sovereign financing instrument aimed at broadening public participation in state funding and deepening the domestic Islamic capital market. Since its initial issuance in 2008 (SR-001), retail sukuk has demonstrated consistent growth in investor numbers, subscription value, and geographic distribution. This study aims to analyze the development trends of SR up to the latest issuance in 2024 (SR-020), identify key challenges hindering its expansion, and formulate strategic in recommendations to enhance retail investor participation. This research adopts a descriptive qualitative approach using literature review methods. Secondary data were obtained from official reports published by the Ministry of Finance (DJPPR), the Financial Service Authority (OJK), sukuk issuance statistics, scholarly articles, and Islamic capital market reports. The findings indicate that despite growing public interest in SR, several challenges persist, including low levels of Islamic financial literacy, strong preferences for conventional instrument, limited digital sharia-compliant distribution channels, and the underdevelopment of a secondary SR market. The study recommends several strategic measures : expanding digital marketing and subscription platforms through e-SBN, enhancing public literacy and education on Islamic finance, introducing more flexible and attractive sukuk product innovations, and providing fiscal incentives and investment frameworks based on Islamic ESG principles. These findings offer valuable insights for regulators, market players, and academics in strengthening retail sukuk as an inclusive and sustainable Islamic financial instrument within Indonesia???s financial ecosystem. Key words: Retail Sukuk, Islamic Finance, financial inclusion, retail investors, policy strategy